Diaphragm and preparation method thereof, conductive slurry and flow battery
By applying a conductive coating composed of proton conductive polymer and sulfonate on one side of the flow battery separator, the problem of self-discharge of the flow battery is solved, and a higher Coulomb efficiency and a longer service life are achieved.
Patent Information
- Application Number
- CN202411821109.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-28
AI Technical Summary
There is self-discharge phenomenon during the charging and discharging of the liquid flow battery, which leads to a reduction in Coulomb efficiency and affects performance and service life.
A separator is provided, including a base film and a conductive coating provided on the base film side. The components of the conductive coating include a proton conductive polymer and a sulfonate. By providing a conductive coating on the base film side, convective mass transfer is inhibited, free convection of ions is blocked, and mass transfer across the membrane of ions of different valence states is reduced.
Effectively suppress the self-discharge phenomenon in the flow battery, improve Coulomb efficiency, improve charge and discharge efficiency and cycle life, and at the same time enhance the puncture strength of the diaphragm and reduce contact resistance.
Smart Images

Figure SMS_7
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a diaphragm and a preparation method thereof, a conductive slurry and a flow battery. Background Art
[0002] Liquid flow batteries are electrochemical energy storage devices that are widely used in various energy storage and conversion fields. Liquid flow batteries have attracted much attention due to their high safety, long cycle life, large energy storage capacity and high energy efficiency. However, liquid flow batteries have self-discharge during the charging and discharging process, which leads to a decrease in coulombic efficiency and affects the performance and service life of liquid flow batteries. Summary of the invention
[0003] Based on this, it is necessary to provide a diaphragm and a preparation method thereof, a conductive slurry and a flow battery that can inhibit the self-discharge of a flow battery.
[0004] In one aspect of the present application, a separator is provided, comprising a base membrane and a conductive coating disposed on at least one side of the base membrane, wherein components of the conductive coating include a proton conductive polymer and a sulfonate.
[0005] The above-mentioned diaphragm improves the selective permeability function of the diaphragm by providing a conductive coating on at least one side of the base membrane. The conductive coating can inhibit convective mass transfer and block the free convection of ions. It effectively inhibits the transmembrane mass transfer of ions of different valence states in the liquid flow battery without affecting the normal migration of ions and electrode reactions, reduces cross contamination, reduces self-discharge, and thus improves the coulombic efficiency of the liquid flow battery. The components of the above-mentioned conductive coating include proton conductive polymers and sulfonates. The proton conductive polymer has a proton conduction effect and can promote proton transfer, while the sulfonate has a sulfonic acid group and can serve as a proton source or provide a channel for proton conduction, further promoting proton transfer. The proton conductive polymer and the sulfonate cooperate with each other and synergistically enhance the effect, which can not only promote the migration of protons, inhibit the transmembrane mass transfer of ions of different valence states, and improve the coulombic efficiency of the liquid flow battery, but also improve the charge and discharge efficiency and cycle life of the liquid flow battery.
[0006] The above-mentioned diaphragm has good comprehensive performance and high puncture strength. The conductive coating can enhance the puncture strength of the diaphragm, thereby improving the coulombic efficiency and comprehensive performance without sacrificing the mechanical strength and conductivity of the diaphragm. The above-mentioned conductive coating can enhance the puncture strength of the diaphragm, so that the battery stack can achieve a higher electrode compression ratio and reduce contact resistance, thereby further improving the performance and service life of the liquid flow battery.
[0007] The conductive coating of the above-mentioned diaphragm is a proton-rich conductive polymer. By controlling the thickness of the conductive coating, the surface resistance of the diaphragm during the charge and discharge process of the liquid flow battery can be controlled, and then the comprehensive performance of the liquid flow battery can be optimized by controlling the thickness of the conductive coating.
[0008] Through the above-mentioned membrane, the coulombic efficiency can be improved without complex adjustments and improvements to multiple components of the flow battery, thereby reducing the production cost and production cycle of the flow battery.
[0009] The above-mentioned diaphragm is highly practical and can be applied to various liquid flow battery systems in acidic systems, such as all-vanadium liquid flow battery, iron-chromium liquid flow battery and zinc-bromine liquid flow battery, etc., and has broad application prospects.
[0010] In some embodiments, the proton conductive polymer includes at least one of polyaniline, polypyrrole, polythiophene and polydopamine; and / or the sulfonate includes at least one of sodium dodecyl sulfonate, sodium lignin sulfonate and sodium benzene sulfonate.
[0011] In some embodiments, the proton conductive polymer includes polyaniline, and the sulfonate includes sodium dodecylbenzene sulfonate; or
[0012] The proton conductive polymer includes polypyrrole, and the sulfonate includes sodium lignin sulfonate.
[0013] In some embodiments, the conductive coating comprises 0.8 to 1.5 parts by weight of a proton conductive polymer and 0.1 to 1.0 parts by weight of a sulfonate.
[0014] In some embodiments, the conductive coating comprises 1 to 1.2 parts by mass of a proton conductive polymer and 0.5 to 1.0 parts by mass of a sulfonate.
[0015] In some embodiments, the conductive coating has a thickness of 10 μm to 500 μm.
[0016] In a second aspect of the present application, a conductive paste is provided, the components of which include a proton conductive polymer, a sulfonate and an organic solvent.
[0017] In some embodiments, the conductive paste satisfies any of the following conditions:
[0018] (1) The proton conductive polymer comprises at least one of polyaniline, polypyrrole, polythiophene and polydopamine;
[0019] (2) The sulfonate comprises at least one of sodium dodecyl sulfonate, sodium lignin sulfonate and sodium benzene sulfonate;
[0020] (3) The organic solvent includes at least one of N-formyl dimethylamide, N-methylpyrrolidone and dimethyl sulfoxide;
[0021] (4) In terms of weight parts, the proton conductive polymer is 0.8 to 1.5 parts, the sulfonate is 0.1 to 1.0 parts, and the organic solvent is 10 to 15 parts.
[0022] The third aspect of the present application provides a method for preparing a diaphragm, comprising the following steps:
[0023] The conductive paste according to the second aspect is coated on at least one side of the base film and dried to form a conductive coating.
[0024] The fourth aspect of the present application provides a liquid flow battery, comprising the diaphragm as described in the first aspect or the diaphragm prepared by the preparation method as described in the fourth aspect. DETAILED DESCRIPTION
[0025] In order to facilitate understanding of the present application, the present application will be described more comprehensively below with reference to the relevant embodiments. The preferred embodiments of the present application are provided in the specific implementation manner, but the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0027] The current solution to the self-discharge phenomenon of flow batteries is to reduce the self-discharge phenomenon by optimizing the battery structure and materials. Some of them try to improve the Coulomb efficiency of flow batteries by improving the composition and concentration of the electrolyte, adjusting the composition and structure of the electrode materials, and optimizing the assembly process of the battery. In addition, some reduce the self-discharge phenomenon by introducing new diaphragm materials. Although the above methods can reduce the self-discharge phenomenon of flow batteries to a certain extent, they often require complex adjustments and improvements to multiple components of the battery, which not only increases the production cost but also prolongs the production cycle; and even after the optimization of the above methods, the self-discharge phenomenon of flow batteries cannot be completely eliminated, especially in the case of long-term storage or high-frequency charging and discharging, the self-discharge problem is still more serious. In addition, although the traditional diaphragm optimization technology can suppress the self-discharge phenomenon of flow batteries to a certain extent, it often sacrifices other properties of the diaphragm, such as mechanical strength and conductivity, thereby affecting the overall performance of the battery. Therefore, how to find a simple and effective method to suppress the self-discharge phenomenon of flow batteries and improve the Coulomb efficiency of flow batteries is a huge challenge currently faced.
[0028] Based on this, one embodiment of the present application provides a separator, comprising a base membrane and a conductive coating disposed on at least one side of the base membrane, wherein components of the conductive coating include a proton conductive polymer and a sulfonate.
[0029] Proton conducting polymers are a class of polymers that can conduct protons (H + ) polymer materials, whose chemical structure contains chemical groups or atoms that can provide proton sources or proton transfer channels, such as: -NH- groups, N atoms, -SO3H groups, catechol structures and protonated amino groups.
[0030] The above-mentioned diaphragm improves the selective permeability function of the diaphragm by providing a conductive coating on at least one side of the base membrane. The conductive coating can inhibit convective mass transfer and block the free convection of ions. It effectively inhibits the transmembrane mass transfer of ions of different valence states in the liquid flow battery without affecting the normal migration of ions and electrode reactions, reduces cross contamination, reduces self-discharge, and thus improves the coulombic efficiency of the liquid flow battery. The components of the above-mentioned conductive coating include proton conductive polymers and sulfonates. The proton conductive polymer has a proton conduction effect and can promote proton transfer, while the sulfonate has a sulfonic acid group and can serve as a proton source or provide a channel for proton conduction, further promoting proton transfer. The proton conductive polymer and the sulfonate cooperate with each other and synergistically enhance the effect, which can not only promote the migration of protons, inhibit the transmembrane mass transfer of ions of different valence states, and improve the coulombic efficiency of the liquid flow battery, but also improve the charge and discharge efficiency and cycle life of the liquid flow battery.
[0031] The above-mentioned diaphragm has good comprehensive performance and high puncture strength. The conductive coating can enhance the puncture strength of the diaphragm, thereby improving the coulombic efficiency and comprehensive performance without sacrificing the mechanical strength and conductivity of the diaphragm (the conductivity can reach above 0.009S / cm). The above-mentioned conductive coating can enhance the puncture strength of the diaphragm, so that the battery stack can achieve a higher electrode compression ratio and reduce contact resistance, thereby further improving the performance and service life of the liquid flow battery.
[0032] The conductive coating of the above-mentioned diaphragm is a proton-rich conductive polymer. By controlling the thickness of the conductive coating, the surface resistance of the diaphragm during the charge and discharge process of the liquid flow battery can be controlled, and then the comprehensive performance of the liquid flow battery can be optimized by controlling the thickness of the conductive coating.
[0033] Through the above-mentioned membrane, the coulombic efficiency can be improved without complex adjustments and improvements to multiple components of the flow battery, thereby reducing the production cost and production cycle of the flow battery.
[0034] The above-mentioned diaphragm is highly practical and can be applied to various liquid flow battery systems in acidic systems, such as all-vanadium liquid flow battery, iron-chromium liquid flow battery and zinc-bromine liquid flow battery, etc., and has broad application prospects.
[0035] In some embodiments, the proton conducting polymer includes at least one of polyaniline, polypyrrole, polythiophene and polydopamine.
[0036] In some embodiments, the sulfonate includes at least one of sodium dodecyl sulfonate, sodium lignin sulfonate and sodium benzene sulfonate.
[0037] In some embodiments, the proton conductive polymer includes polyaniline, and the sulfonate includes sodium dodecylbenzene sulfonate; or
[0038] The proton conductive polymer includes polypyrrole, and the sulfonate includes sodium lignin sulfonate. The conductive coating of this component makes the selective permeation function of the diaphragm better, further reduces the self-discharge phenomenon of the flow battery, and makes the battery coulomb efficiency higher.
[0039] In some embodiments, the conductive coating includes 0.8 to 1.5 parts of proton conductive polymer and 0.1 to 1.0 parts of sulfonate by weight. The proton conductive polymer and the sulfonate have good compatibility with each other at this weight ratio, and synergistically enhance the efficiency, which can further improve the coulombic efficiency of the flow battery, and further improve the charge and discharge efficiency and cycle life of the flow battery.
[0040] As an example, the mass fraction of the proton conductive polymer can be 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4 and 1.5 parts, or can be within the range consisting of any two of the above points as end values. Optionally, the mass fraction of the proton conductive polymer is 1 to 1.2 parts.
[0041] As an example, the mass fraction of the sulfonate can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 and 1.0, or can be within the range consisting of any two of the above points as end values. Optionally, the mass fraction of the sulfonate is 0.5 to 1.0.
[0042] In some embodiments, the conductive coating includes 1 to 1.2 parts of proton conductive polymer and 0.5 to 1.0 parts of sulfonate by weight. The proton conductive polymer and sulfonate can further reduce the self-discharge phenomenon, improve the coulombic efficiency, and the comprehensive performance of the separator is also better at this mass ratio.
[0043] In some embodiments, the thickness of the conductive coating is 10 μm to 500 μm. The conductive coating is a proton-rich conductive polymer. Controlling the thickness of the conductive coating can control the surface resistance of the diaphragm during the charge and discharge process of the flow battery, and thus the overall performance of the flow battery can be optimized by controlling the thickness of the conductive coating.
[0044] As an example, the thickness of the conductive coating can be 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 150μm, 200μm, 250μm, 300μm, 350μm, 400μm, 450μm, 500μm, or it can be within the range formed by any two of the above point values as end values. The thickness of the conductive coating is preferably 30μm ~100μm. Controlling the thickness of the conductive coating to 30μm ~100μm can further reduce the self-discharge phenomenon of the liquid flow battery and enable the liquid flow battery to obtain better electrical and mechanical properties.
[0045] In some embodiments, the base membrane may be a perfluorosulfonic acid homogeneous membrane, a reinforced membrane, a microporous membrane, or other diaphragm with ion screening function.
[0046] In some embodiments, the base film has a thickness of 10 μm to 500 μm.
[0047] In a second aspect of the present application, a conductive paste is provided, the components of which include a proton conductive polymer, a sulfonate and an organic solvent.
[0048] In some embodiments, the proton conducting polymer includes at least one of polyaniline, polypyrrole, polythiophene and polydopamine.
[0049] In some embodiments, the sulfonate includes at least one of sodium dodecyl sulfonate, sodium lignin sulfonate and sodium benzene sulfonate.
[0050] In some embodiments, the organic solvent includes at least one of N-formyl dimethylamide, N-methylpyrrolidone and dimethyl sulfoxide.
[0051] In some embodiments, the proton conductive polymer includes polyaniline, and the sulfonate includes sodium dodecylbenzene sulfonate; or
[0052] The proton conductive polymer includes polypyrrole, and the sulfonate includes sodium lignin sulfonate. The self-discharge phenomenon of the all-vanadium liquid flow battery prepared by the conductive slurry with the raw material components and mass ratio is significantly reduced, the battery coulomb efficiency is higher, and the mechanical properties and conductive properties of the diaphragm are better.
[0053] In some embodiments, based on weight percentage, the proton conductive polymer is 0.8 to 1.5 parts, the sulfonate is 0.1 to 1.0 parts, and the organic solvent is 10 to 15 parts.
[0054] As an example, the mass fraction of the proton conductive polymer can be 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4 and 1.5 parts, or can be within the range consisting of any two of the above points as end values. Optionally, the mass fraction of the proton conductive polymer is 1 to 1.2 parts.
[0055] As an example, the mass fraction of the sulfonate can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 and 1.0, or can be within the range consisting of any two of the above points as end values. Optionally, the mass fraction of the sulfonate is 0.5 to 1.0.
[0056] As an example, the mass fraction of the organic solvent can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts and 15 parts, or can be within a range consisting of any two of the above points as end values.
[0057] In some embodiments, the components of the conductive paste include the following components in mass fractions: 1 to 1.2 parts of a proton conductive polymer, 0.5 to 1.0 parts of a sulfonate, and 10 to 15 parts of an organic solvent. The proton conductive polymer, the sulfonate, and the organic solvent interact with each other in this mass ratio, have good compatibility, and synergize to further improve the coulombic efficiency of the flow battery, and further improve the charge and discharge efficiency and cycle life of the flow battery.
[0058] In some embodiments, the conductive paste comprises the following components by mass: 1 to 1.2 parts of polyaniline, 0.5 to 1.0 parts of sodium dodecylbenzene sulfonate, and 10 to 15 parts of N-methylpyrrolidone. The conductive coating made of the conductive paste further improves the selective permeability of the diaphragm, effectively suppresses the self-discharge phenomenon, and improves the coulombic efficiency of the battery.
[0059] In some embodiments, the conductive paste includes the following components: polyaniline, sodium lignin sulfonate and an organic solvent.
[0060] In some embodiments, the conductive paste includes the following components: polyaniline, sodium benzyl sulfonate, and an organic solvent.
[0061] In some embodiments, the conductive paste includes the following components: polypyrrole, sodium dodecyl sulfate and an organic solvent. The conductive coating made from the conductive paste further suppresses the self-discharge phenomenon and improves the coulombic efficiency of the battery.
[0062] In some embodiments, the conductive paste includes the following components: polypyrrole, sodium pyrrole sulfonate, and an organic solvent.
[0063] In some embodiments, the conductive paste includes the following components: polythiophene, sodium dodecyl sulfate and an organic solvent.
[0064] In some embodiments, the conductive paste includes the following components: polythiophene, sodium lignin sulfonate and an organic solvent.
[0065] In some embodiments, the conductive paste includes the following components: polythiophene, sodium benzenesulfonate, and an organic solvent.
[0066] In some embodiments, the conductive paste includes the following components: polydopamine, sodium dodecyl sulfate and an organic solvent.
[0067] In some embodiments, the conductive paste includes the following components: polydopamine, sodium lignin sulfonate and an organic solvent.
[0068] In some embodiments, the raw materials for preparing the conductive paste include the following components: polydopamine, sodium benzylsulfonate and an organic solvent.
[0069] In some embodiments, the method for preparing the conductive paste comprises the following steps:
[0070] The proton conductive polymer, the sulfonate and the organic solvent are mixed according to the composition for 1 hour to 3 hours to prepare the conductive paste.
[0071] During the mixing process, ball milling, ultrasonic vibration or mechanical stirring can be used to mix the raw material components evenly.
[0072] In some embodiments, a conductive coating is provided, wherein the components of the conductive coating include a proton conductive polymer and a sulfonate; or,
[0073] The conductive coating is made from the conductive paste described in the second aspect.
[0074] The third aspect of the present application provides a method for preparing a diaphragm, comprising the following steps:
[0075] The conductive paste according to the second aspect is coated on at least one side of the base film and dried to form a conductive coating.
[0076] Furthermore, the separator is a battery separator, and the conductive slurry as described in the second aspect is coated on one side or both sides of the battery separator and dried to form a conductive coating.
[0077] Furthermore, the thickness of the conductive coating on one side or both sides of the battery separator is 10 μm to 500 μm.
[0078] Furthermore, it is preferred to spray the conductive coating on both sides of the diaphragm. It is also possible to select whether to spray on one side or both sides and the spraying thickness according to the positive electrode, negative electrode and the degree of cross-membrane migration of the electrolyte in the flow battery.
[0079] A fourth aspect of the present application provides a liquid flow battery, comprising the diaphragm as described in the first aspect or the diaphragm prepared by the preparation method as described in the third aspect.
[0080] Flow batteries include, but are not limited to, all-vanadium flow batteries, iron-chromium flow batteries, and zinc-bromine flow batteries.
[0081] It can be understood that the liquid flow battery includes not only the above-mentioned diaphragm, but also a positive electrode, a negative electrode and an electrolyte, and the diaphragm is arranged between the positive electrode and the negative electrode.
[0082] The active material of the all-vanadium flow battery is vanadium ions of different valence states dissolved in aqueous solution. The main component of the electrolyte is vanadium sulfate salt solution. The conversion between electrical energy and chemical energy is achieved through the change of the valence of vanadium ions. The positive electrode of the all-vanadium flow battery usually uses carbon materials such as graphite felt and carbon cloth, and the negative electrode can also use carbon materials such as graphite felt.
[0083] The positive electrolyte of the all-vanadium flow battery is composed of pentavalent vanadium ions (V 5+ ) and tetravalent vanadium ions (V 4+ ) of sulfuric acid solution, where V 5+ and V 4+ Ions in acidic solution are Ions and In the charging process, Ions lose electrons to form ions and hydrogen ions; during discharge, Ions are generated by electrons Ions and water, during the reaction, hydrogen ions migrate between the positive and negative electrodes through the diaphragm to maintain charge balance.
[0084] The negative electrode electrolyte of the all-vanadium flow battery is composed of trivalent vanadium ions (V 3+ ) and divalent vanadium ions (V 2+ ) of sulfuric acid solution. When charging, V 3+ The ion gets the electron to generate V 2+ ions; when discharging, V 2+ Ions lose electrons to form V 3+ ion.
[0085] When the diaphragm of the present application is used in an all-vanadium liquid flow battery, it can effectively inhibit the transmembrane mass transfer of vanadium ions of different valence states in the all-vanadium liquid flow battery, reduce cross contamination, and thereby improve the coulombic efficiency of the all-vanadium liquid flow battery.
[0086] Iron-chromium flow battery: The active materials are iron ions and chromium ions. The electrolyte is usually a mixed solution of ferrous chloride, chromium chloride, etc. The redox reaction of iron-chromium ions is used for charging and discharging.
[0087] Zinc-bromine flow battery: The active materials are zinc and bromine, and the electrolyte is zinc bromide solution. During charging, zinc ions are reduced to metallic zinc at the negative electrode and deposited on the electrode surface, and bromide ions are oxidized to bromine gas at the positive electrode. The opposite is true during discharge.
[0088] The present application also provides an electrical device, comprising the liquid flow battery as described in the fourth aspect.
[0089] Electrical devices include, but are not limited to, electric vehicles, electric ships, solar inverters, and wind turbine converters.
[0090] The present application also provides an energy storage device, comprising the liquid flow battery as described in the fourth aspect.
[0091] Energy storage devices include, but are not limited to, solar power generation systems, wind power generation systems, grid energy storage systems, and uninterruptible power supply (UPS) systems.
[0092] The following are specific embodiments.
[0093] Example 1
[0094] A conductive paste is prepared by raw materials comprising the following components in parts by mass: 1 part of polyaniline, 1 part of sodium dodecylbenzene sulfonate, and 10 parts of N-methylpyrrolidone.
[0095] According to the composition of the above-mentioned raw materials, polyaniline, sodium dodecylbenzene sulfonate and N-methylpyrrolidone were mixed for 3 hours to prepare a uniform conductive paste.
[0096] A perfluorosulfonic acid diaphragm with a size of 20 cm × 20 cm and a thickness of 50 μm was selected; the conductive slurry was evenly sprayed on the surface of the cleaned perfluorosulfonic acid diaphragm using a spraying device with a spraying thickness of 15 μm; after the spraying was completed, the diaphragm was placed in a vacuum drying oven and dried at 80°C for 12 hours to obtain a diaphragm with a conductive coating.
[0097] Example 2
[0098] Example 2 is basically the same as Example 1, except that the spraying thickness of the conductive paste is 50 μm.
[0099] Example 3
[0100] Example 3 is substantially the same as Example 1, except that the amount of sodium dodecylbenzene sulfonate is 0.5 parts.
[0101] Example 4
[0102] Embodiment 4 is substantially the same as embodiment 1, except that polyaniline is replaced by polypyrrole of equal mass.
[0103] Example 5
[0104] Example 5 is substantially the same as Example 1, except that an equal amount of polydopamine is used to replace polyaniline.
[0105] Example 6
[0106] Example 6 is substantially the same as Example 1, except that an equal amount of sodium lignin sulfonate is used to replace sodium dodecylbenzene sulfonate.
[0107] Comparative Example 1
[0108] Comparative Example 1 is substantially the same as Example 1, except that the diaphragm is not sprayed with conductive slurry.
[0109] Comparative Example 2
[0110] Comparative Example 2 is substantially the same as Example 1, except that sodium dodecylbenzene sulfonate is omitted from the conductive paste.
[0111] The diaphragms of Examples 1-6 and Comparative Examples 1-2 were placed in an all-vanadium liquid flow battery stack, and the assembled stack was subjected to performance testing. The test results are shown in Table 1 below.
[0112] All-vanadium liquid flow battery charge and discharge performance test conditions: temperature 26 ° C, test voltage range 1.0V~1.6V, current density 160mA cm -2 .
[0113] Diaphragm puncture strength test standard or test conditions: NB / T 42080-2023.
[0114] Table 1
[0115]
[0116] As can be seen from Table 1 above, the all-vanadium redox flow batteries prepared in Examples 1 to 6 not only have high coulombic efficiency and reduced self-discharge, but also have high voltage efficiency and high energy efficiency, and at the same time have high diaphragm puncture strength and good mechanical strength. The coulombic efficiency, voltage efficiency, energy efficiency and diaphragm puncture strength of Examples 1 to 6 are all higher than those of Comparative Examples 1 to 2.
[0117] When the mass fraction of polyaniline in the conductive slurry is 1 to 1.2 parts and the mass fraction of sodium dodecylbenzene sulfonate is 0.5 to 1.0 parts, the coulombic efficiency of the prepared all-vanadium liquid flow battery is as high as 98.18%; in addition, the effect is better when the thickness of the diaphragm coating is 30μm to 100μm, and the coulombic efficiency of the all-vanadium liquid flow battery is as high as 99.01%.
[0118] It can also be seen from Comparative Example 2 that the proton conductive polymer and the sulfonate in the conductive coating cooperate with each other and synergistically enhance the effect. Without one of the components, the effect of the present application cannot be achieved.
[0119] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0120] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A diaphragm, characterized in that: The invention comprises a base film and a conductive coating layer arranged on at least one side of the base film, wherein components of the conductive coating layer include a proton conductive polymer and a sulfonate.
2. The diaphragm according to claim 1, characterized in that The proton conductive polymer includes at least one of polyaniline, polypyrrole, polythiophene and polydopamine; and / or the sulfonate includes at least one of sodium dodecyl sulfonate, sodium lignin sulfonate and sodium benzene sulfonate.
3. The diaphragm according to claim 1, characterized in that The proton conductive polymer includes polyaniline, and the sulfonate includes sodium dodecylbenzenesulfonate; or, The proton conductive polymer includes polypyrrole, and the sulfonate includes sodium lignin sulfonate.
4. The diaphragm according to any one of claims 1 to 3, characterized in that: The conductive coating comprises 0.8 to 1.5 parts of a proton conductive polymer and 0.1 to 1.0 parts of a sulfonate by weight.
5. The diaphragm according to claim 4, characterized in that The conductive coating comprises 1 to 1.2 parts of a proton conductive polymer and 0.5 to 1.0 parts of a sulfonate by weight.
6. The diaphragm according to any one of claims 1 to 3, characterized in that The thickness of the conductive coating is 10 μm to 500 μm.
7. A conductive paste, characterized in that: Its components include proton conductive polymer, sulfonate and organic solvent.
8. The conductive paste according to claim 7, characterized in that: Satisfy any of the following: (1) The proton conductive polymer comprises at least one of polyaniline, polypyrrole, polythiophene and polydopamine; (2) The sulfonate comprises at least one of sodium dodecyl sulfonate, sodium lignin sulfonate and sodium benzene sulfonate; (3) The organic solvent includes at least one of N-formyl dimethylamide, N-methylpyrrolidone and dimethyl sulfoxide; (4) In terms of weight parts, the proton conductive polymer is 0.8 to 1.5 parts, the sulfonate is 0.1 to 1.0 parts, and the organic solvent is 10 to 15 parts.
9. A method for preparing a diaphragm, characterized in that: The steps include: The conductive paste according to any one of claims 7 to 8 is coated on at least one side of the base film and dried to form a conductive coating.
10. A liquid flow battery, characterized in that: The invention comprises the diaphragm as described in claims 1 to 6 or the diaphragm prepared by the preparation method as described in claim 9.